“Art and aesthetic experience: john dewey” (2014)
The question for the arts, is a matter that, rather than the artists themselves, has troubled psychologists, anthropologists, historians and, especially among many other scholars, philosophers. It is precisely from the perspective of the latter –the philosophy of art–, that this question will be discussed, based on the look of the famous American pragmatist John Dewey. It is concluded firsthand that, in order to interpret the Deweyan thinking, it is necessary to refer to a philosophicalepistemological category called Experience, which, will come into line with the aesthetics: a quality that –according to Dewey– give shape and substance to the concept of aesthetic experience.